The study of disease pattern of various clinical classes of hemophilia in South Gujarat area, India - Shah, Vijay B.; Bansal, Niraj; Mehta, Kirti (International Journal of Contemporary Pediatrics, 2019)
Background: Haemophilia is one of the most severe bleeding disorder. Seventy-five per cent of the global haemophiliacs live in developing countries, where probably only one in five cases is diagnosed, and there is little or no care available. Haemophilia as a disease and its management has a large impact on the community, including social integration and economics. Inability to be an active part of society and high cost of the medical care make this disease an important problem for all haemophilic patients. Methodology: a cross-sectional study, conducted over a period of one and half year. Institutional Ethics Committee permission was taken before starting the study. Information was gathered through personal interview of the patient’s guardian with the help of predesigned questionnaires. Special emphasis was given to past history of bleeding. For each specific symptom/ specific site a detailed history and relevant details was taken and number of episodes of each symptom or number of episodes of involvement of a specific site was written. Observations: Out of 75 patients of haemophilia; 8 (10.7%) were Mild haemophilic, 17 (22.7%) were moderate haemophilic; and 50 (66.7%) were severe haemophilic. Most common site for spontaneous bleeding was muscle where 121 (25%) episodes of bleeding were reported, followed by knee joint 97(20%), and Ankle 79 (16.3%). The commonest site for traumatic bleeding was muscle where 201 (24.7%) episodes of bleeding were reported, followed by knee joint 175 (21.5%), Ankle 143 (17.6%) and Elbow joint 83 (10.2%). Site with highest duration of bleeding was intracranial for 6 days. Conclusion: Frequency of traumatic dental and nasal bleeds was significantly higher in mild class as compared to moderate and severe classes. In severe category Knee, ankle, elbow and muscle were the commonest site where traumatic bleeding. There was no significant difference in bleeding frequencies at various sites in moderate and severe cases, whether spontaneous or traumatic bleed.